Unraveling the pathways of sustainable music education: a moderated mediation analysis of environmental awareness, pedagogical approaches, and student engagement - Luo, Kun; Wang, Yi (Frontiers in Psychology, 2025)
IntroductionGiven the significance of fostering sustainable practices in music education, the study proposes a relation between sustainable music education (SME) and environmental awareness (EA) in music learning through a moderated mediation mechanism of student engagement (SE) and innovative pedagogical approaches (IPA).MethodsThe study employs a survey-based approach to empirically assess the hypothesized model. Data are collected through questionnaires from a sample of music students in China. Further, data are analyzed using multivariate analytical techniques to establish relationships among these variables.ResultsOur findings indicate that SME exhibits a significant influence on EA and consciousness among music students. Besides, SE significantly mediates the link between SME and EA. Furthermore, IPA moderates the association between SME and EA through the mediator effect of SE, such that at high levels of IPA, the associations are stronger (vice versa).DiscussionThis study contributes to the field of music education by unveiling the pathways through which SME can foster heightened EA. By establishing a moderated mediation model involving SE and IPA, this research highlights the interconnectedness of these variables in the context of music learning.